An Analysis of the Institution of Indentured Servitude in Early Colonial America - Driver, Beau (URJ-UCCS: Undergraduate Research Journal at UCCS, 2011)
This paper presents the economic and social issues that lead to the rise of indentured servitude as a means of acquiring labor in Early Colonial America. The text focuses on the condition in Europe, the conditions for those who crossed the Atlantic, and the condition for the servants in the New World. Also, this text provides a comparison of New England and Virginia and the Middle Colonies with regard to their respective uses of indentured servitude.